2020
DOI: 10.1016/j.btre.2020.e00524
|View full text |Cite
|
Sign up to set email alerts
|

Expression optimization, purification and in vitro characterization of human epidermal growth factor produced in Nicotiana benthamiana

Abstract: Highlights Growth factors play a crucial role in tissue repair and wound healing. Recombinant human epidermal growth factor was produced in N. benthamiana by agroinfiltration. Expression conditions were optimized and the recombinant protein was purified. Plant-produced hEGF facilitate the HaCaT cell proliferation and cell migration in vitro. Plant-produced hEGF can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…Because the investment cost and time for phase 1 cGMP manufacturing of plant expression system are comparatively cost-effective (7.5- to 10-fold) and faster (<6 months) than mammalian expression system, the plant-production platform might be an alternative platform for the production of many biopharmaceutical products. The use of plant expression systems for the production of pharmaceutically important proteins ( Bulaon et al, 2020 ; Hanittinan et al, 2020 ), vaccines ( Marsian et al, 2017 ; Rosales-Mendoza et al, 2017 ), diagnostic reagents ( Rattanapisit et al, 2021 ), and antibodies ( Kopertekh et al, 2019 ; Hurtado et al, 2020 ; Rattanapisit et al, 2020 ) were documented. In addition, the prior studies reported that the generation of plant-made protective immunogen and therapeutic antibodies ( Dent et al, 2016 ; Rattanapisit et al, 2019a , b ; Nessa et al, 2020 ; Yiemchavee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the investment cost and time for phase 1 cGMP manufacturing of plant expression system are comparatively cost-effective (7.5- to 10-fold) and faster (<6 months) than mammalian expression system, the plant-production platform might be an alternative platform for the production of many biopharmaceutical products. The use of plant expression systems for the production of pharmaceutically important proteins ( Bulaon et al, 2020 ; Hanittinan et al, 2020 ), vaccines ( Marsian et al, 2017 ; Rosales-Mendoza et al, 2017 ), diagnostic reagents ( Rattanapisit et al, 2021 ), and antibodies ( Kopertekh et al, 2019 ; Hurtado et al, 2020 ; Rattanapisit et al, 2020 ) were documented. In addition, the prior studies reported that the generation of plant-made protective immunogen and therapeutic antibodies ( Dent et al, 2016 ; Rattanapisit et al, 2019a , b ; Nessa et al, 2020 ; Yiemchavee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant expression systems have several advantages over other expression systems currently in use, such as rapid and high production with the ability to accumulate grams of target protein per kilogram of biomass in less than a week ( Gleba et al, 2005 ; Sainsbury et al, 2009 ; Holtz et al, 2015 ; Maharjan and Choe, 2021 ). This system has been successfully used for the production of functional active complex proteins, such as full length Pfs48/45 of Plasmodium falciparum ( Mamedov et al, 2019b ), human Furin, Factor IX ( Mamedov et al, 2019a ), glycohormone erythropoietin ( Grosse-Holz et al, 2018 ), latent transforming growth factor-beta (TGF-beta) ( Wilbers et al, 2016 ), human epidermal growth factor ( Hanittinan et al, 2020 ), PA83 of B. anthracis ( Mamedov et al, 2016 , 2017 ), HIV gp140, other viral glycoproteins ( Margolin et al, 2018 , 2020a ), and antigens against influenza, Ebola, dengue, rotavirus, and norovirus ( Mett et al, 2008 ; Landry et al, 2014 ; Rybicki, 2014 ; Pêra et al, 2015 ; Takeyama et al, 2015 ). The goal of this study is to lead to the development of a safe, cost effective plant produced ACE2 enzyme with anti-SARS-CoV-2 activities to use in the treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The targeting of the protein to the ER provided a high level of production of a number of complex and difficult to-express proteins in N. benthamiana plant, such as full length Pfs48/45 or Pfs230 of P. falciparum ( Farrance et al, 2011 ; Mamedov et al, 2019b ), heptameric form of protective antigen of B. anthracis , human Furin and Factor IX ( Mamedov et al, 2019a ), and RBD of spike protein of SARS-CoV-2 ( Mamedov et al, 2021 ); human Interleukin 6 ( Nausch et al, 2012 ); hemagglutinin from a range influenza viruses ( Chichester et al, 2009 ); monoclonal antibodies ( Vézina et al, 2009 ; Holtz et al, 2015 ); HIV gp140 ( Margolin et al, 2020a ). In addition, other factors that can provide more target accumulation are Agro optimization ( Shamloul et al, 2014 ; Hanittinan et al, 2020 ; Kaur et al, 2021 ), especially using appropriate target specific Agrobacterium strains ( Norkunas et al, 2018 ), activation of agrobacteria with MES (2-morpholinoethanesulfonic acid), MgCl 2 , Acetosyringone ( Shamloul et al, 2014 ; Kaur et al, 2021 ), and to control humidity, temperature, and light during plant growth ( Shamloul et al, 2014 ). In general, these factors allowed the production of the recombinant soluble form of ACE2 at a high level in the N. benthamiana plant.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that recombinant GCase was successfully produced in WT and ΔgntI N. benthamiana plants ( Figure 1 ). Since Agrobacterium -infiltration conditions usually affect the transformation efficiency, resulting in different expression levels of recombinant protein (Hanittinan et al, 2020 ), two main factors, Agrobacterium cell density and harvest time, were optimized to produce a large amount of GCase with biological activity. Previous studies demonstrated that too low cell density might lead to insufficient Agrobacterium infection, whereas too high density may cause necrosis (Kagale et al, 2012 ; Leuzinger et al, 2013 ; Yan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%